Three-dimensional bipedal DNA walker enabled logic gates responding to telomerase and miRNA. Issue 21 (15th February 2021) - Liu, Xin; Meng, Fanyu; Sun, Rui; Wang, Kangnan; Yu, Zhiqiang; Miao, Peng
Abstract : Gold nanoparticle mediated bipedal DNA walkers are fabricated for logic gate operations responding to telomerase and miRNA. Abstract : In this work, we have developed a simple and reliable platform for simultaneous analysis of telomerase and miRNA. A three-dimensional bipedal DNA walking strategy is designed utilizing gold nanoparticles and MnO2 nanosheets. Given the merits of fast, sensitive and selective analysis, the developed method has great potential application in early clinical diagnosis.